78 - KNOWLEDGE OF MOTHERS ABOUT BREASTFEEDING (Fiep Bulletin - online, 2011)
In breastfeeding, human milk is a dynamic substance and its composition serves to supply the babies´ nutritional necessities, moreover, breastfeeding is an act of love and affection, which contributes to developing biological and psychosocial establishing strong ties between mother and child . The objective of this research was to evaluate mother's perception about breast-feeding and how important is its training. The prospective, descriptive study was conducted with a health unit in the country. of Sao Paulo. The population included 15 mothers with more than 18 years old, all-resident in Limeira city, attended in this health unit that had children born up to 3 months before the interview. As results were observed that the mothers had knowledge on the importance and felt pleasure in breast-feeding. Based on these results we may suggest that offering training about breast-feeding, acts in favor of positive results. As a result it was observed that mothers were aware about the importance of breastfeeding and felt happy to breastfeed. With these results suggest that providing training on breastfeeding promote positive results, with good acceptance of breastfeeding.
Keywords: Breastfeeding; Nursing care; Perception